Segmental cutaneous leukocytoclastic vasculitis associated with herpes zoster: a case report and literature review (Dermatology Reports, 2023)
Varicella zoster virus (VZV) infection may cause large or medium vessel vasculitis, including granulomatous arteritis of the nervous system and central nervous system vasculitis. However, small vessel vasculitis, such as cutaneous leukocytoclastic vasculitis (LCV) associated with localized cutaneous VZV infection, herpes zoster, is uncommon. Herein, we present the case of a 75-year-old man with segmental leukocytoclastic vasculitis associated with herpes zoster on the leg. To the best of our knowledge, there are four cases of segmental leukocytoclastic vasculitis in herpes zoster reported in the English literature; we compared our case with these previous reports. Our review of five patients suggests that most patients were immunosuppressed. We also found that the leg is susceptible to LCV associated with herpes zoster. Anti-viral treatment was effective for LCV as well as herpes zoster. Prior reports have proposed etiologies inducing LCV; for example, immune complexes are mediated by vessel wall damage. In support of this, histopathology in our case showed a C3-positive reaction with the small vessel walls in the dermis in direct immunofluorescence. Although the mechanism of LCV associated with herpes zoster remains unclear, we should consider LCV while diagnosing and treating patients with herpes zoster, especially immunosuppressed patients.